1991
DOI: 10.1002/cne.903090309
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic architecture of nucleus ambiguus motoneurons projecting to the upper alimentary tract in the rat

Abstract: The motor innervation for palatal, pharyngeal, laryngeal, and esophageal muscles originates within the nucleus ambiguus. Although the viscerotopic organization of the upper alimentary tract in the nucleus ambiguus has been extensively studied, little information concerning the dendritic arborization of nucleus ambiguus motoneurons is available. The neural tracer cholera toxin-horseradish peroxidase, which is particularly effective at revealing dendrites of retrogradely labeled neurons, was used to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
52
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 42 publications
9
52
0
Order By: Relevance
“…The nucleus ambiguus comprises four major subdivisions that can be differentiated on the basis of their cytoarchitecture and efferent connections (Molhant, 1912;Lawn, 1966;Bieger and Hopkins, 1987;Hopkins, 1987;Altschuler et al, 1991;Kitamura et al, 1993). The subdivisions of the nucleus ambiguus, namely, a rostra1 esophagomotor compact formation, an intermediate pharyngomotor semicompact formation, a caudal laryngomotor loose formation, and a general visceromotor external formation (Bieger and Hopkins, 1987), have different roles in swallowing, respiration, vocalization, and autonomic function.…”
Section: Indexing Terms: Pharyngeal Motoneurons Laryngeal Motoneuronmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleus ambiguus comprises four major subdivisions that can be differentiated on the basis of their cytoarchitecture and efferent connections (Molhant, 1912;Lawn, 1966;Bieger and Hopkins, 1987;Hopkins, 1987;Altschuler et al, 1991;Kitamura et al, 1993). The subdivisions of the nucleus ambiguus, namely, a rostra1 esophagomotor compact formation, an intermediate pharyngomotor semicompact formation, a caudal laryngomotor loose formation, and a general visceromotor external formation (Bieger and Hopkins, 1987), have different roles in swallowing, respiration, vocalization, and autonomic function.…”
Section: Indexing Terms: Pharyngeal Motoneurons Laryngeal Motoneuronmentioning
confidence: 99%
“…In comparison to esophagomotor neurons of the compact formation, the somata of motoneurons of the rat semicompact and loose formations are more diffusely distributed, spanning up to 2.5 mm in the ventrolateral medulla. In addition, the dendritic arbors of these cells extend beyond the borders of the nucleus, unlike those of the compact formation, indicating the possibility for the convergence of a wider range of inputs with a varied complement of synapses capable of a more finely modulated control (Altschuler et al, 1991). Here we describe the morphology and structural relationships of neurons situated within the rat semicompact and loose formations of the nucleus ambiguus that project to the pharynx and larynx, respectively.…”
mentioning
confidence: 95%
“…The AmC is a well defined cell column situated in the rostral half of the nucleus ambiguus, and composed of mainly medium-sized neurons containing well-developed cell organelles, longitudinally orientated dendritic bundles, axon terminals, and small neurons having a small rim of cytoplasm (Bieger and Hopkins, 1987;Hopkins, 1995;Hayakawa et al, 1996). Ultrastructural retrograde tracing studies have also shown that there are four kinds of neurons in the AmC, that is, cervical esophageal motoneurons, subdiaphragmatic esophageal motoneurons, small neurons which are not projecting to the alimentary canal, and a few pharyngeal motoneurons in the rostral part of the AmC (Bieger and Hopkins, 1987;Altschuler et al, 1991;Hopkins, 1995;Hayakawa et al, 1996). The esophageal motoneurons are characterized by somato-somatic, somato-dendritic, or dendro-dendritic apposition by adherent junctions (Hopkins, 1995;Hayakawa et al, 1996).…”
mentioning
confidence: 97%
“…Based on cytoarchitecture and innervation of target organs as revealed by retrograde tracing studies, it has been shown that the nucleus ambiguus is composed of compact, semicompact, loose, and external formations (Bieger and Hopkins, 1987;Altschuler et al, 1991). The esophageal motoneurons are located in the compact formation of the nucleus ambiguus (AmC; Lawn, 1966;Yoshida et al, 1981;Holstege et al, 1983;Fryscak et al, 1984;Bieger and Hopkins, 1987;Kitamura et al, 1993).…”
mentioning
confidence: 97%
See 1 more Smart Citation